THE ROLE OF THE SCIENTIFIC OVERVIEWS IN THE GENERIC DRUG REGISTRATION PROCESS IN THE RUSSIAN FEDERATION AND EURASIAN ECONOMIC UNION - K. S. Milchakov (Разработка и регистрация лекарственных средств, 2019)
Background: Non-clinical and clinical overviews are an obligatory part of the Common Technical Document, that is the new format of the registration dossier in the Russian Federation and Eurasian Economic Union. Development of the overview demands on specific skills of the literature search and critical appraisal and also of systematization of scientific data. Goal of the paper consists of the description of the latest legislative rules about the development of the reviews for generic drug application by Russian national and EAEU rules and also practical experience of SMA LitReview. Conclusions: The review is one of the key elements of the generic drug dossier now in the Russian Federation and EAEU. In some cases, the review can replace the results of own trials of the Sponsor. Review process demands skills of the use of the international bibliographic databases, critical appraisal, good academic writing skills and also knowledge of modern Russian and EAEU law.